Joseph L. Angel, Otherworldly and Eschatological Priesthood in the Dead Sea Scrolls (Studies on the Texts of the Desert of Judah 86; Leiden: Brill, 2010) - Drawnel, Henryk (The Biblical Annals, 2015)
Book review: Joseph L. Angel, Otherworldly and Eschatological Priesthood in the Dead Sea Scrolls (Studies on the Texts of the Desert of Judah 86; Leiden: Brill, 2010). Pp. xiii, 380. € 133. ISBN 978-90-04-18145-8.